Consumer behavior on the media market - Martin Přibyl; Ladislav Stejskal; Ondřej Dufek; Klára Ondrášková (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2009)
The paper deals with a correlation between factors identifying a household representative and frequency of media usage. Particularly it concentrates on the analysis of internet and daily press usage. Internet is a constantly developing communication channel which is increasingly used in the field of marketing communication and contributes to the development of business environment. Due to its characteristics it is an ideal mean for multilingual communication and communication on international markets. The daily press is on the other hand a representative of traditional media. It is perceived by public as a more natural communication channel. The paper seeks an answer to the question which communication channel is more suitable to communicate with a particular target group – press or the internet. The paper tests the correlation between identification factors and frequency of internet and press presence. Testing will be carried out by using a database obtained in a primary research conducted by the Department of Marketing and Trade at the Faculty of Business and Economics, Mendel University in Brno. Results published in the paper are part of research objective, id. code: 62156 48904 “The Czech Republic in the process of integration and globalization and the evolution of agrarian and service sectors in the new conditions of the European integrated market”, thematic area 03 “The evolution of trade relationships regarding changes in a life style and purchasing behaviour and changes of business environment in the process of integration and globalization” that is conducted with a financial support of Ministry of Education, Youth and Sports.